Method for preparing filamentous pseudo-boehmite through standing sedimentation and aging and filamentous pseudo-boehmite

Through static sedimentation and aging treatment, the carbonized liquid is mixed with hot water to separate the nano-colloidal particles and micron particles, forming a suitable inducing environment to promote the directional growth of the nano-colloidal particles, solving the problems of uneven morphology and low crystal purity in traditional methods, and realizing the preparation of high-quality filamentous pseudo-boehmite.

CN120817619AActive Publication Date: 2025-10-21CHALCO SHANDONG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511053448.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-10-21
Estimated Expiration
2045-07-30

AI Technical Summary

Technical Problem

Existing technologies make it difficult to precisely control the morphology and crystal purity of filamentous pseudo-boehmite. Traditional methods are complex and easily affected by fluctuations in reaction conditions, resulting in poor product quality stability.

Method used

Through static sedimentation and aging treatment, the carbonized liquid is mixed with water at a preset temperature to separate the nano-colloidal particles and micron-particles, forming a suitable inducing environment to promote the directional growth of the nano-colloidal particles and form a filamentous structure with a high aspect ratio. Aging treatment is then carried out in a pure environment to ensure morphological uniformity and crystal phase purity.

Benefits of technology

The high aspect ratio morphology control and high crystal phase purity of filamentous pseudo-boehmite are achieved. The product morphology distribution is uniform, the crystallinity reaches 50% to 60%, and the grain size is excellent, which is suitable for high-end application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120817619A_ABST
    Figure CN120817619A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aluminum oxide material preparation, in particular to a method for preparing filamentous pseudo-boehmite through standing sedimentation and aging and filamentous pseudo-boehmite. The method comprises the following steps: carrying out carbonization reaction on carbon dioxide and a sodium aluminate solution to obtain a carbonized solution; according to a preset volume ratio, mixing water with a preset temperature with the carbonized liquid to obtain mixed slurry; wherein the temperature of the water is higher than that of the carbonization liquid; the mixed slurry is subjected to standing sedimentation and solid-liquid separation in sequence, micron particles are separated, and supernatant liquid is obtained; performing aging treatment on the supernatant liquid to obtain aged slurry; and carrying out post-treatment on the aged slurry to obtain the filamentous pseudo-boehmite. According to the method, the physical and chemical property difference of carbonization liquid components is utilized, enrichment and oriented growth of target nano colloidal particles are achieved through hot water temperature control treatment, standing settling separation and aging treatment, and finally the filamentous pseudo-boehmite product with good morphology and low impurity content is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of alumina material preparation, and in particular to a method for preparing filamentous pseudo-boehmite by static sedimentation and aging, and the filamentous pseudo-boehmite. Background Art

[0002] As a critical alumina precursor, pseudo-boehmite has broad application potential in many fields such as catalyst supports, adsorbents, and ceramic materials due to its unique physical and chemical properties. Pseudo-boehmite has diverse morphologies, including spherical, filamentous, spindle-shaped, and filamentous forms. Pseudo-boehmite with different morphologies exhibits different performance in applications. Among these pseudo-boehmites, filamentous pseudo-boehmite has obvious advantages in certain high-end application scenarios due to its unique aspect ratio and high specific surface area. However, the difficulty of preparing filamentous pseudo-boehmite is the most prominent among all morphologies.

[0003] Traditional pseudo-boehmite preparation methods involve complex, multi-step reaction processes, such as aluminum salt precipitation, which requires precise control of solution pH, reaction temperature, and the rate of precipitant addition, resulting in cumbersome operational procedures. While hydrothermal synthesis can currently be used to control the pseudo-boehmite product's crystal phase and save on reaction time, the resulting crystal phase purity is low, and the pseudo-boehmite product is often contaminated with other impurities. This makes the pseudo-boehmite product's particle morphology susceptible to fluctuations in reaction conditions, making precise control difficult. These factors contribute to the poor quality and stability of the pseudo-boehmite product. Summary of the Invention

[0004] The present application provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging, and the filamentous pseudo-boehmite, to solve the following technical problem: how to simultaneously improve the crystal phase purity and morphology distribution of the pseudo-boehmite product.

[0005] In a first aspect, an embodiment of the present application provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging, the method comprising:

[0006] Carbon dioxide and sodium aluminate solution are carbonized to obtain a carbonized liquid containing nano-colloidal particles and micron particles;

[0007] Mixing water at a preset temperature and the carbonized liquid containing the nano-colloidal particles and the micron-particles in a preset volume ratio to preliminarily induce the nano-colloidal particles to grow in a directional manner to form a filamentous structure, thereby obtaining a mixed slurry containing the nano-colloidal particles, the filamentous structure, and the micron-particles; wherein the temperature of the water is greater than the temperature of the carbonized liquid;

[0008] The mixed slurry containing nano-colloid particles, filamentous structures and micron particles is subjected to static sedimentation and solid-liquid separation in sequence to separate the micron particles and obtain a supernatant liquid;

[0009] performing an aging treatment on the supernatant to allow the nano-colloidal particles and the filamentous structure to grow in a directional manner to form filamentous pseudo-boehmite, thereby obtaining an aged slurry;

[0010] The aged slurry is post-treated to obtain filamentous pseudo-boehmite.

[0011] Optionally, the preset volume ratio is 1:(0.5 to 2.5); and / or

[0012] The preset temperature is 70°C to 100°C.

[0013] Optionally, the temperature of the mixed slurry is 55°C to 95°C.

[0014] Optionally, the temperature of the aging treatment is 70° C. to 80° C., and the time of the aging treatment is 4 h to 6 h.

[0015] Optionally, the static sedimentation time is 15 minutes to 60 minutes.

[0016] Optionally, the static sedimentation time is 20 minutes to 60 minutes.

[0017] Optionally, the mass concentration of aluminum oxide in the carbonization liquid is 0.5 g / L to 6 g / L.

[0018] Optionally, the post-processing of the aged slurry to obtain filamentous pseudo-boehmite comprises the following steps:

[0019] Performing solid-liquid separation on the aged slurry to obtain a solid-phase aged material;

[0020] washing the solid-phase aged material to obtain a washed material;

[0021] The washed material is dried to obtain filamentous pseudo-boehmite.

[0022] In the second aspect, the embodiment of the present application provides a filamentous pseudo-boehmite, which is prepared by the method described in the first aspect, and the crystallinity of the filamentous pseudo-boehmite is 50% to 60%, and the grain size of the filamentous pseudo-boehmite is to The mass of the gibbsite in the filamentous pseudo-boehmite is 0.5% to 1.0% of the mass of the filamentous pseudo-boehmite.

[0023] Optionally, the length of the whiskers of the filamentous pseudo-boehmite is 5 μm to 15 μm, the diameter of the whiskers of the filamentous pseudo-boehmite is 0.2 μm to 2.0 μm, and the aspect ratio of the whiskers of the filamentous pseudo-boehmite is 5 to 20.

[0024] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0025] The embodiment of the present application provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging. This technology achieves water dispersion and heats the carbonized liquid by precisely controlling the volume ratio of water and carbonized liquid at a preset temperature, thereby creating an induction environment with excellent dispersibility and suitable temperature. This environment helps to preliminarily guide the nano-colloidal particles to grow in a specific direction to form a filamentous structure. Subsequently, by the method of static sedimentation, the Brownian motion of the filamentous structure and nano-colloidal particles, as well as the agglomeration static sedimentation effect between micron particles, are utilized to achieve effective separation of micron particles from the filamentous structure and nano-colloidal particles. Finally, the supernatant obtained by separation is subjected to aging treatment, and by adjusting the temperature and pH, the filamentous structure and nano-colloidal particles are promoted to grow stably into a one-dimensional chain structure, and finally a filamentous pseudo-boehmite product with a highly uniform morphological distribution is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0028] Figure 1 A schematic flow chart of a method for preparing filamentous pseudo-boehmite by static sedimentation and aging provided in an embodiment of the present application;

[0029] Figure 2 A detailed flow chart of a method for preparing filamentous pseudo-boehmite by static sedimentation and aging provided in an embodiment of the present application;

[0030] Figure 3 A scanning electron microscope diagram of a filamentous pseudo-boehmite product prepared by a method for preparing filamentous pseudo-boehmite by static sedimentation and aging provided in Example 1 of the present application;

[0031] Figure 4This is a schematic diagram of a scanning electron microscope of a filamentous pseudo-boehmite product prepared by a method for preparing filamentous pseudo-boehmite by static sedimentation and aging provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0032] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0033] The range descriptions described in this application, such as numerical ranges, ratio ranges, etc., include all possible sub-ranges and single numerical values ​​within the range. For example, the range description of "1 to 6" or "1~6" covers all sub-ranges from 1 to 6 (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6). Unless otherwise specified, the terms "including" and "including" used in this article mean "including but not limited to"; relational terms such as "first" and "second" are only used to distinguish different entities or operations, and do not imply an actual sequence or association relationship; "and / or" means that multiple situations can exist alone or simultaneously; expressions such as "at least one", "multiple", and "at least one" refer to any combination of corresponding objects, including a combination of single or multiple objects. The proportional relationships involved in the text, such as mass ratios, molar ratios, etc., should be understood as the corresponding relationship between the first and second terms of the proportional formula in the order of description. The raw materials, reagents, instruments and equipment used in this article can be purchased on the market or prepared by existing methods.

[0034] It should be noted that the inventors have discovered the following problems with the prior art described in the background art:

[0035] (1) Difficulty in directional shape control:

[0036] Traditional hydrothermal synthesis methods struggle to precisely induce the growth of nanoparticles into high-aspect-ratio filamentous structures, and are prone to producing heterogeneous or non-uniform morphologies. Therefore, the temperature of the carbonization solution and hot water used in the traditional hydrothermal synthesis process needs to be controlled, and the mixing ratio of the two needs to be optimized to create a suitable slurry environment. This promotes the preferential growth of nanoparticles along specific crystal planes, achieving precise control of the aspect ratio of the filamentous pseudo-boehmite morphology. This also prevents morphological damage caused by dissolution and recrystallization of the nanoparticles.

[0037] (2) Impurity phase suppression bottleneck:

[0038] During the hydrothermal synthesis process, gibbsite Al(OH)3 is easily formed, which seriously affects the crystal purity of the pseudo-boehmite product. Furthermore, high-purity filamentous pseudo-boehmite requires the gibbsite content to be controlled at ≤1.0%. Therefore, how to optimize the aging process to improve the phase transition path of the nanoparticles and effectively inhibit the formation of gibbsite?

[0039] (3) Conflict between process efficiency and stability:

[0040] Traditional hydrothermal synthesis relies on multi-step reaction control, such as pH adjustment and precipitant addition, making the overall operation cumbersome and complex. Therefore, there is an urgent need to explore innovative approaches that can achieve efficient separation of nanocolloids from micron-sized particles through static sedimentation of the carbonized solution, combined with an aging process to produce filamentous pseudo-boehmite. However, these micron-sized particles are prone to forming gibbsite, which affects the crystalline purity of the pseudo-boehmite.

[0041] Based on the above-mentioned shortcomings of the prior art, the present application provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging. This method achieves the following goals by precisely controlling the alumina concentration of the carbonized liquid, the mixing temperature, the static sedimentation time, and the aging conditions:

[0042] 1. Breakthrough in filament morphology control: By synergistically controlling the temperature between the carbonized liquid and water at a preset temperature, the nanoparticles in the carbonized liquid are induced to grow in a directional manner into filamentous structures with a high aspect ratio, overcoming the uneven particle morphology defects of traditional methods.

[0043] 2. Improve product crystal purity and performance: optimize the mixed slurry temperature (≥65℃) and aging conditions (70℃ to 80℃), inhibit the formation of gibbsite (content ≤1.0%), and increase the crystallinity of pseudo-boehmite (50% to 60%) and grain size ( to ) to ensure the uniformity of the filament morphology (length of 5 μm to 15 μm, diameter of 0.2 μm to 2 μm).

[0044] Figure 1 A schematic flow chart of a method for preparing filamentous pseudo-boehmite by static sedimentation and aging provided in an embodiment of the present application is exemplarily shown;

[0045] like Figure 1 As shown, the embodiment of the present application provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging, the method comprising:

[0046] S1. Carbon dioxide and sodium aluminate solution are carbonized to obtain a carbonized liquid containing nano-colloidal particles and micron particles;

[0047] S2. Mixing water at a preset temperature and the carbonized liquid containing the nano-colloidal particles and the micronized particles in a preset volume ratio to preliminarily induce the nano-colloidal particles to grow in a directional manner to form a filamentous structure, thereby obtaining a mixed slurry containing the nano-colloidal particles, the filamentous structure, and the micronized particles; wherein the temperature of the water is greater than the temperature of the carbonized liquid;

[0048] S3. The mixed slurry containing nano-colloid particles, filamentous structures and micron particles is sequentially subjected to static sedimentation and solid-liquid separation to separate the micron particles to obtain a supernatant;

[0049] S4. The supernatant is aged so that the nano-colloidal particles and the filamentous structure grow in a directional manner to form filamentous pseudo-boehmite to obtain an aged slurry;

[0050] S5. Post-processing the aged slurry to obtain filamentous pseudo-boehmite.

[0051] It should be noted that the present invention provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging. This method utilizes the differences in the physical and chemical properties of the carbonized liquid components and achieves the enrichment and directional growth of target nanoparticles through a step-by-step process (hot water temperature control treatment + static sedimentation separation + aging), while eliminating micronized particles. The specific mechanism of this method is as follows:

[0052] 1. Two-component characteristics of carbonization reaction products:

[0053] When carbon dioxide reacts with sodium aluminate solution, an amorphous aluminum hydroxide precipitate (i.e., pseudo-boehmite precursor) is formed. This reaction process usually produces a polydisperse particle system consisting of:

[0054] 1) Nanoparticles: They are very small (usually a few nanometers to tens of nanometers), have high surface energy, are in a metastable or metastable state, are sensitive to aging conditions, and are the target precursors for the formation of the final filamentous product.

[0055] 2) Micronized particles: These are larger (usually in the micron range) and relatively more stable. They are agglomerates or impurity phases that form rapidly during the reaction (possibly containing impurities such as silicon and iron, or irregular large particles formed by premature and disordered agglomeration of nanoparticles). These micronized particles generally lack the ability to form ideal filamentous morphologies and are prone to crystallization into gibbsite.

[0056] 2. Hot water mixing and static sedimentation separation (key impurity removal and enrichment steps):

[0057] Warm water mixing with preset volume ratio: Using hot water with a temperature higher than that of the carbonized liquid, its core function is to reduce the viscosity of the system and introduce mild thermal convection.

[0058] 1) Reduce viscosity: It is more conducive to the movement and static sedimentation of micron particles (according to Stokes' law, the static sedimentation rate is inversely proportional to the viscosity).

[0059] 2) Mild thermal convection: promotes collisions between particles, but not so violent as to destroy the structure or cause excessive turbulence.

[0060] 3. Static sedimentation mechanism (separation of nano-particles and micron particles):

[0061] (1) Gravity difference dominates: Micron particles are large in size and relatively high in density, and are prone to forming dense flocs that settle quickly under the action of gravity.

[0062] 1) Brownian motion maintains suspension: Nanoparticles are extremely small and are subject to strong Brownian motion. Their thermal motion energy is sufficient to resist gravity sedimentation and can be stably suspended in the upper liquid phase for a long time.

[0063] 2) Synergy of temperature effect: The temperature environment maintained by hot water helps to maintain the colloidal stability of nanoparticles (preventing premature flocculation) while accelerating the static sedimentation kinetics of large particles.

[0064] (2) Solid-liquid separation results:

[0065] 1) Supernatant: This primarily contains highly concentrated, uniformly sized nanoparticles, along with dissolved sodium aluminate and carbonates. The micronized particles effectively settle to the bottom and are removed from the sediment. This step significantly improves the crystalline purity of the material being processed.

[0066] 2) Bottom slurry: contains micron particles that settle down after standing.

[0067] 4. Aging treatment (key to directional growth of filamentous morphology):

[0068] (1) Enriched and purified nanoparticle environment: The supernatant contains almost only target nanoparticles, eliminating the interference of micron particles. These nanoparticles have:

[0069] 1) High surface energy: drives the ripening process.

[0070] Small and relatively uniform size: provides a good starting point for subsequent directional growth.

[0071] (2) Directed growth mechanism of aging process:

[0072] 1) Aging: Under aging temperature and time, the system tends to reduce the total surface energy. The smaller nanoparticles with higher solubility gradually dissolve, and the dissolved aluminum species Al(OH)4 - Migrate and deposit on the surface of larger or more stable particles.

[0073] 2) Directed attachment: The dissolution-redeposition process tends to proceed along specific crystal planes. Under suitable aging conditions (temperature, pH, ionic strength, and the absence of impurities), nanoparticles tend to connect and grow through directed attachment. That is, they approach each other and align and bond according to a specific crystallographic orientation, forming a one-dimensional chain structure.

[0074] 3) Inhibition of isotropic growth: Temperature-controlled aging conditions in a weakly alkaline environment (usually controlling the temperature in a weakly alkaline environment) are conducive to the stabilization and growth of specific crystal planes, inhibiting the growth rate in other directions, thereby promoting the development of one-dimensional filamentous or fibrous morphology.

[0075] 4) Uniform environment promotes uniform morphology: Because the supernatant is relatively pure and has a narrow particle size distribution, all nanoparticles experience a highly similar growth environment. This greatly promotes consistency in growth rate and direction, ultimately resulting in a product with a highly uniform filamentous morphology.

[0076] 5.Mechanism of simultaneously improving crystal purity and morphology:

[0077] (1) Improved crystal purity: The static sedimentation separation step effectively physically separates and removes the micron particles from the target nano-colloidal particles (supernatant). The target of the subsequent aging treatment is the purified nano-colloidal particle system.

[0078] (2) Improved morphology distribution uniformity:

[0079] 1) Precursor homogenization: After static sedimentation and separation, the precursor entering aging is relatively uniform in size nanoparticles. This provides a uniform, high-quality "seed" for subsequent directional growth.

[0080] 2) Eliminate interference: Micronized particles (which may become heterogeneous nucleation centers or interfere with the directional attachment process) and impurity ions (which may adsorb on specific crystal planes and change the growth rate or cause defects) are removed, creating a pure chemical environment that is conducive to uniform and directional growth.

[0081] 3) Optimizing growth conditions: Based on pure and uniform precursors, precisely controlled aging conditions (temperature, time, pH) further ensure that the filamentous morphology grows stably and uniformly along the target direction.

[0082] In summary, the present invention provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging, which has the following mechanism:

[0083] 1. Carbonization produces two components (nano-colloidal particles + micron particles / impurities).

[0084] 2. Hot water mixing promotes static sedimentation: large / mixed micron particles quickly settle to the bottom and are separated and discarded → obtaining a supernatant rich in pure nano-colloidal particles → significantly improving the purity of the crystal phase.

[0085] 3. Pure and uniform nanoparticles undergo directional growth (aging + directional attachment) under optimized aging conditions → forming a uniform filamentous morphology.

[0086] Therefore, the embodiment of the present application provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging. This method first regulates the carbonization liquid by hot water to form a good inducing environment, and then achieves the enrichment and purification of the target precursor (nano-colloidal particles) and the effective removal of impurities / interference phases (micron particles) through a relatively simple physical static sedimentation step, laying a decisive foundation for the subsequent directional growth of nano-colloidal particles into a uniform filamentous structure in a pure and uniform environment, thereby simultaneously improving the crystal phase purity and morphology distribution uniformity of the product.

[0087] In some optional embodiments, the preset volume ratio is 1:(0.5 to 2.5); and / or

[0088] The preset temperature is 70°C to 100°C.

[0089] In these embodiments, a preset volume ratio of 1:(0.5 to 2.5) can increase the temperature of the carbonized liquid by using water at a preset temperature, introducing gentle thermal convection, while simultaneously reducing the viscosity of the carbonized liquid system, providing a certain inductive environment for the carbonized liquid, allowing the nano-colloidal particles to grow in a directional manner to form a filamentous structure. Additionally, a preset temperature of 70°C to 100°C allows the water to effectively increase the temperature of the carbonized liquid and reduce the viscosity of the carbonized liquid system, allowing the nano-colloidal particles to grow in a directional manner to form a filamentous structure.

[0090] The preset volume may be 1:0.5, 1:1.0, 1:1.5, 1:2.0 or 1:2.5.

[0091] The preset temperature may be 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.

[0092] In some optional embodiments, the temperature of the mixed slurry is 55°C to 95°C.

[0093] In these embodiments, the mixed slurry at a temperature of 55° C. to 95° C. can maintain the stability of the nano-colloidal particles and the filamentous structure, facilitating the subsequent separation of the nano-colloidal particles, the filamentous structure and the micronized particles by static sedimentation, thereby obtaining a pure supernatant.

[0094] The temperature of the mixed slurry may be 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C.

[0095] In some optional embodiments, the temperature of the aging treatment is 70° C. to 80° C., and the time of the aging treatment is 4 h to 6 h.

[0096] In these embodiments, aging treatment at a temperature of 70°C to 80°C and for 4 to 6 hours can promote the stable growth of filamentous structures and nano-colloidal particles into one-dimensional chain structures, and ultimately produce a filamentous pseudo-boehmite product with a highly uniform morphology distribution.

[0097] The temperature of the aging treatment may be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C.

[0098] The aging treatment time can be 4 hours, 4.5 hours, 5.0 hours, 5.5 hours or 6.0 hours.

[0099] In some optional embodiments, the static sedimentation time is 15 minutes to 60 minutes.

[0100] In these embodiments, the static sedimentation time of 15 minutes to 60 minutes can promote the agglomeration static sedimentation effect between the micron particles to have sufficient time to form agglomerates of the micron particles, thereby achieving physical separation between the micron particles, filamentous structures and nano-colloidal particles, improving the crystal phase purity of the pseudo-boehmite in the supernatant, and facilitating the subsequent aging treatment to form filamentous pseudo-boehmite.

[0101] The static sedimentation time can be 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.

[0102] In some optional embodiments, the static sedimentation time is 20 minutes to 60 minutes.

[0103] In these embodiments, the static sedimentation time of 20 to 60 minutes can further achieve physical separation between micron particles, filamentous structures and nano-colloidal particles, and improve the crystal phase purity of the supernatant, facilitating subsequent aging treatment to form filamentous pseudo-boehmite.

[0104] The static sedimentation time can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.

[0105] In some optional embodiments, the mass concentration of aluminum oxide in the carbonization liquid is 0.5 g / L to 6 g / L.

[0106] In these embodiments, the carbonization liquid having an aluminum oxide mass concentration of 0.5 g / L to 6 g / L can provide sufficient aluminum oxide components, thereby facilitating the formation of sufficient nano-colloidal particles in the subsequent mixing stage.

[0107] The mass concentration of aluminum oxide in the carbonized liquid can be 0.5 g / L, 1.0 g / L, 1.5 g / L, 2.0 g / L, 2.5 g / L, 3.0 g / L, 3.5 g / L, 4.0 g / L, 4.5 g / L, 5.0 g / L, 5.5 g / L or 6.0 g / L.

[0108] In some optional embodiments, the post-processing of the aged slurry to obtain filamentous pseudo-boehmite comprises the steps of:

[0109] S501. The aged slurry is subjected to solid-liquid separation to obtain a solid-phase aged material;

[0110] S502. Washing the solid phase aged material to obtain a washed material;

[0111] S503. Dry the washed material to obtain filamentous pseudo-boehmite.

[0112] In these embodiments, the filamentous pseudo-boehmite formed in the aged slurry can be separated and purified by solid-liquid separation, washing, and drying, thereby obtaining filamentous pseudo-boehmite with excellent crystal purity and morphology.

[0113] like Figure 3 As shown, the embodiment of the present application exemplarily shows a filamentous pseudo-boehmite

[0114] Based on a general concept, such as Figure 3 As shown, the embodiment of the present application provides a filamentous pseudo-boehmite, which is prepared by the method described in the first aspect, and the crystallinity of the filamentous pseudo-boehmite is 50% to 60%, and the grain size of the filamentous pseudo-boehmite is to The mass of the gibbsite in the filamentous pseudo-boehmite is 0.5% to 1.0% of the mass of the filamentous pseudo-boehmite.

[0115] The filamentous pseudo-boehmite is prepared based on the above method. The specific steps of the method can be referred to the above embodiment. Since the filamentous pseudo-boehmite adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here.

[0116] It should be noted that the crystallinity is 50% to 60% and the grain size is to The filamentous pseudo-boehmite indicates that the filamentous pseudo-boehmite has an excellent crystal phase; in addition, the mass of gibbsite is 0.5% to 1.0% of the mass of the filamentous pseudo-boehmite, which indicates that the filamentous pseudo-boehmite has a lower impurity content and a higher crystal phase purity.

[0117] In some optional embodiments, the length of the whiskers of the filamentous pseudo-boehmite is 5 μm to 15 μm, the diameter of the whiskers of the filamentous pseudo-boehmite is 0.2 μm to 2.0 μm, and the aspect ratio of the whiskers of the filamentous pseudo-boehmite is 5 to 20.

[0118] In these embodiments, the filamentous pseudo-boehmite has a whisker length of 5 μm to 15 μm, a whisker diameter of 0.2 μm to 2.0 μm, and an aspect ratio of 5 to 20, indicating that the filamentous pseudo-boehmite has a good morphology.

[0119] The present application is further described below with reference to specific examples. Experimental methods in the following examples where specific conditions are not specified are generally measured in accordance with national / industry standards. If there are no corresponding national / industry standards, the methods are carried out in accordance with commonly used international standards, conventional conditions, or conditions recommended by the manufacturer.

[0120] Example 1

[0121] like Figure 2 As shown, a method for preparing filamentous pseudo-boehmite by static sedimentation and aging comprises:

[0122] S1. Carbon dioxide and sodium aluminate solution are carbonized to obtain a carbonized liquid containing nano-colloidal particles and micron particles at a temperature of 42 ° C;

[0123] S2. Mixing water at a preset temperature and a carbonized liquid containing nano-colloidal particles and micronized particles in a preset volume ratio to preliminarily induce directional growth of the nano-colloidal particles to form a filamentous structure, thereby obtaining a mixed slurry containing nano-colloidal particles, filamentous structures, and micronized particles; wherein the temperature of the water is greater than the temperature of the carbonized liquid;

[0124] S3. The mixed slurry containing nano-colloids, filamentous structures and micron particles was sequentially subjected to static sedimentation and solid-liquid separation to separate the micron particles to obtain a supernatant;

[0125] S4. The supernatant was aged to allow the nano-colloidal particles and the filamentous structure to grow in a directional manner to form filamentous pseudo-boehmite to obtain an aged slurry;

[0126] S501. The aged slurry is subjected to solid-liquid separation to obtain a solid phase aged material;

[0127] S502. The solid phase aged material is washed to obtain a washed material;

[0128] S503. Dry the washed material to obtain filamentous pseudo-boehmite.

[0129] The preset volume ratio is 1:1.0;

[0130] The preset temperature is 70℃.

[0131] The temperature of the mixed slurry was 56°C.

[0132] The aging temperature is 75°C and the aging time is 4 hours.

[0133] The settling time is 20 minutes.

[0134] The mass concentration of aluminum oxide in the carbonization solution is 5.0 g / L.

[0135] Example 2

[0136] Compared with Example 1, this embodiment has the following differences, and the rest are the same:

[0137] The preset volume ratio is 1:2.5;

[0138] The preset temperature is 100℃.

[0139] The temperature of the mixed slurry was 83°C.

[0140] The aging temperature is 80°C and the aging time is 6 hours.

[0141] The settling time is 30 minutes.

[0142] The mass concentration of aluminum oxide in the carbonization solution is 0.5 g / L.

[0143] Example 3

[0144] Compared with Example 1, this embodiment has the following differences, and the rest are the same:

[0145] The preset volume ratio is 1:2.0;

[0146] The preset temperature is 95℃.

[0147] The temperature of the mixed slurry was 77°C.

[0148] The aging treatment temperature is 70°C and the aging treatment time is 5 h.

[0149] The settling time is 60 minutes.

[0150] The mass concentration of aluminum oxide in the carbonization solution is 6 g / L.

[0151] Example 4

[0152] Compared with Example 1, this embodiment has the following differences, and the rest are the same:

[0153] The preset volume ratio is 1:0.5;

[0154] The preset temperature is 85℃.

[0155] The temperature of the mixed slurry was 56°C.

[0156] The aging treatment temperature is 75°C and the aging treatment time is 5 h.

[0157] The settling time is 40 minutes.

[0158] The mass concentration of aluminum oxide in the carbonization solution is 3.0 g / L.

[0159] Example 5

[0160] Compared with Example 1, this embodiment has the following differences, and the rest are the same:

[0161] The preset volume ratio is 1:2.0;

[0162] The preset temperature is 70℃.

[0163] The temperature of the mixed slurry was 61°C.

[0164] The aging treatment temperature is 78°C and the aging treatment time is 6 hours.

[0165] The settling time is 45 minutes.

[0166] The mass concentration of aluminum oxide in the carbonization solution is 2.0 g / L.

[0167] Comparative Example 1

[0168] Compared with Example 1, the differences of this comparative example are as follows, and the rest are the same:

[0169] The carbonized liquid is not mixed with water of a preset temperature and then allowed to settle, but is directly aged. The specific steps are as follows:

[0170] S1. Carbon dioxide and sodium aluminate solution are carbonized to obtain a carbonized liquid containing nano-colloidal particles and micron particles;

[0171] S2. The carbonized liquid is aged to allow the nano-colloidal particles and the filamentous structure to grow in a directional manner to form filamentous pseudo-boehmite to obtain an aged slurry;

[0172] S3. The aged slurry is subjected to solid-liquid separation to obtain a solid phase aged material;

[0173] S4. The solid phase aged material is washed to obtain a washing material;

[0174] S5. Drying the washed material to obtain filamentous pseudo-boehmite.

[0175] The mass concentration of aluminum oxide in the carbonization solution is 2.0 g / L.

[0176] The aging treatment temperature is 78°C and the aging treatment time is 6 hours.

[0177] Comparative Example 2

[0178] Compared with Example 1, the differences of this comparative example are as follows, and the rest are the same:

[0179] The mixed slurry is directly aged without using a static settling operation.

[0180] Comparative Example 3

[0181] Compared with Example 1, the differences of this comparative example are as follows, and the rest are the same:

[0182] The preset temperature is the same as the temperature of the carbonized liquid itself.

[0183] Comparative Example 4

[0184] Compared with Example 1, the differences of this comparative example are as follows, and the rest are the same:

[0185] The preset volume ratio is 1:0.2.

[0186] Comparative Example 5

[0187] Compared with Example 1, the differences of this comparative example are as follows, and the rest are the same:

[0188] The preset volume ratio is 1:3.0.

[0189] Related experiments and effect data:

[0190] 1. Analyze and collect the filamentous pseudo-boehmite products of Example 1 and Comparative Example 1, and count their morphological characteristics. The results are as follows: Figure 3 and Figure 4 As shown by Figure 3 and Figure 4 It can be seen that the method for preparing filamentous pseudo-boehmite by static sedimentation and aging provided in the embodiments of the present application can obtain a filamentous pseudo-boehmite product with more uniform morphology distribution and clear filamentous structure, which shows that this method can obtain a filamentous pseudo-boehmite product with good morphology.

[0191] 2. The filamentous pseudo-boehmite products of each embodiment and comparative example were statistically analyzed, and their microscopic morphologies and impurity contents were statistically analyzed. The results are shown in Table 1.

[0192] Table 1 Microscopic morphology and impurity content of the filamentous pseudo-boehmite products of each embodiment

[0193]

[0194] As shown in Table 1, the present invention provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging. The method utilizes the differences in the physical and chemical properties of the carbonized liquid components and achieves the enrichment and directional growth of the target nano-colloidal particles through step-by-step treatment (hot water temperature control treatment + static sedimentation separation + aging). The final filamentous pseudo-boehmite product has a crystallinity of more than 50% and a grain size of The above, at the same time, the average length of the whiskers of the final filamentous pseudo-boehmite product is more than 5.0 μm, and the average diameter of the filamentous pseudo-boehmite product is 0.43 μm; in addition, the gibbsite impurity content in the final filamentous pseudo-boehmite product is 1.0% or less.

[0195] In summary, the embodiments of the present application provide a method for preparing filamentous pseudo-boehmite by static sedimentation and aging. This method utilizes the differences in the physical and chemical properties of the carbonized liquid components and achieves the enrichment and directional growth of the target nano-colloidal particles through step-by-step treatment (hot water temperature control treatment + static sedimentation separation + aging), ultimately obtaining a filamentous pseudo-boehmite product with good morphology and low impurity content.

[0196] In addition, the present invention provides a method for preparing filamentous pseudo-boehmite by static sedimentation and aging. This method, based on a coordinated control system of hot water and carbonizing liquid, can create an environment for the directional growth of nano-colloidal particles, producing filamentous pseudo-boehmite products with a high aspect ratio. This method effectively solves the technical problems of uneven morphology and interference from impurities in traditional processes.

[0197] In addition, the filamentous pseudo-boehmite provided in the embodiments of the present application has good structural uniformity and can provide a basic raw material with excellent performance for high-end fields such as catalyst carriers and precision adsorption materials.

[0198] In addition, the crystallinity of the filamentous pseudo-boehmite provided in the embodiment of the present application can reach 50% to 60%, and the grain size is maintained at to Moreover, the crystal phase purity and structural stability of filamentous pseudo-boehmite are significantly better than those of the traditional hydrothermal method, which can meet the stringent requirements of high-temperature catalysis, special ceramics and other fields for high-temperature resistance and high stability of materials.

[0199] The foregoing is merely a detailed description of the present invention, intended to enable those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein, but rather is intended to conform to the broadest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing filamentous pseudo-boehmite by static sedimentation and aging, the method comprising: Carbon dioxide and sodium aluminate solution are subjected to carbonization reaction to obtain a carbonized liquid containing nano-colloidal particles and micron particles; Mixing water at a preset temperature and the carbonized liquid containing the nano-colloidal particles and the micron-particles in a preset volume ratio to preliminarily induce the nano-colloidal particles to grow in a directional manner to form a filamentous structure, thereby obtaining a mixed slurry containing the nano-colloidal particles, the filamentous structure, and the micron-particles; wherein the temperature of the water is greater than the temperature of the carbonized liquid; The mixed slurry containing nano-colloid particles, filamentous structures and micron particles is subjected to static sedimentation and solid-liquid separation in sequence to separate the micron particles and obtain a supernatant liquid; performing an aging treatment on the supernatant to allow the nano-colloidal particles and the filamentous structure to grow in a directional manner to form filamentous pseudo-boehmite, thereby obtaining an aged slurry; The aged slurry is post-treated to obtain filamentous pseudo-boehmite.

2. The method according to claim 1, characterized in that The preset volume ratio is 1:(0.5 to 2.5); and / or The preset temperature is 70°C to 100°C.

3. The method according to claim 1, characterized in that The temperature of the mixed slurry is 55°C to 95°C.

4. The method according to claim 1, wherein The temperature of the aging treatment is 70° C. to 80° C., and the time of the aging treatment is 4 hours to 6 hours.

5. The method according to claim 1, wherein The time for the static sedimentation is 15 min to 60 min.

6. The method according to claim 5, characterized in that The time for the static sedimentation is 20 min to 60 min.

7. The method according to claim 1, characterized in that The mass concentration of aluminum oxide in the carbonization liquid is 0.5 g / L to 6 g / L.

8. The method according to claim 1, characterized in that The post-processing of the aged slurry to obtain filamentous pseudo-boehmite comprises the following steps: Performing solid-liquid separation on the aged slurry to obtain a solid-phase aged material; washing the solid-phase aged material to obtain a washed material; The washed material is dried to obtain filamentous pseudo-boehmite.

9. A filamentous pseudo-boehmite, wherein the filamentous pseudo-boehmite is prepared by the method according to any one of claims 1 to 8, wherein the crystallinity of the filamentous pseudo-boehmite is 50% to 60%, and the grain size of the filamentous pseudo-boehmite is to The mass of the gibbsite in the filamentous pseudo-boehmite is 0.5% to 1.0% of the mass of the filamentous pseudo-boehmite.

10. The filamentous pseudo-boehmite according to claim 9, characterized in that The length of the whisker of the filamentous pseudo-boehmite is 5 μm to 15 μm, the diameter of the whisker of the filamentous pseudo-boehmite is 0.2 μm to 2.0 μm, and the aspect ratio of the whisker of the filamentous pseudo-boehmite is 5 to 20.

Citation Information

Patent Citations

  • Preparation method for pseudo-boehmite and preparation method for gamma-alumina

    CN106315642A

  • Preparation method of macroporous pseudo-boehmite

    CN118954557A

  • Preparation method of ultrafine aluminium hydroxide

    CN1752006A

  • Method of preparing alumina sols from aluminiumchloride solution

    KR1020020044683A